Marketing Strategy In Regional Public Company Bank Perkreditan Rakyat Bank Sumedang - Dedi Setiawan; Syaifuddin Syaifuddin (SINTESA, 2023)
The focus of this research is to examine the phenomenon of marketing strategy at the Regional Public Company of the People's Credit Bank, Bank Sumedang. The purpose of this study is to determine the supporting and inhibiting factors as well as marketing strategy efforts at Perumda BPR Bank Sumedang in increasing income, with the marketing mix approach (Marketing Mix) or 7P, Product, Price, Place, Promotion, People, Physical evidence, and Process, using SWOT analysis, this research method is descriptive qualitative. The data analysis technique used is qualitative data analysis and SWOT analysis. Data collection techniques are interviews, documentation studies, and observation. The results showed that the Marketing Strategy at Perumda BPR Bank Sumedang includes Market Segmentation, Targeting, Positioning, and Differentiation, has been implemented quite well, and one of the Marketing Mix approaches namely Products is a supporting factor for the implementation of marketing strategies where Bank Sumedang is part of completeness of regional autonomy so that the products offered better understand customer desires, while the inhibiting factor in the implementation of marketing strategies is the lack of employees who focus on marketing, in order to increase Bank Sumedang's income to encourage digital transformation to increase competitiveness and get Fee base income. through SWOT analysis shows a very favorable situation for Bank Sumedang because it has opportunities and strengths, so that in this position the company must support an aggressive growth policy.